Measuring corneal clouding in patients suffering from mucopolysaccharidosis with the Pentacam densitometry programme. Issue 7 (17th May 2013) - Elflein, H M; Hofherr, T; Berisha-Ramadani, F; Weyer, V; Lampe, C; Beck, M; Pitz, S
Abstract : Aim: To identify a means to objectively measure corneal clouding in patients with mucopolysaccharidosis in a prospective controlled clinical trial. Methods: Corneal haze was assessed by slit lamp examination and measured using the densitometry programme of the Pentacam, a rotating Scheimpflug camera in 33 mucopolysaccharidoses (MPS) patients and 32 controls. Results: Pentacam measurements were available in 31 right and 31 left eyes of 32 patients and in 32 left and right eyes of 32 subjects in the control group. Slit lamp findings correlated very well with corneal density measurements (Spearman correlation right eye (OD)/left eye (OS)=0.782/0.791). MPS patients had higher density units (median OD/OS=14.1/14.7) than control subjects (median OD/OS=6.7/6.9, p<0.001). In patients, the corneal centre density values (median OD/OS=13.8/14.0) did not differ from corneal periphery values (median OD/OS=14.3/14.7). Conclusions: The densitometry programme of the Pentacam provides objective measurement of corneal haze in mucopolysaccharidosis patients.